Developing a job-based curriculum framework to bridge SKAO gaps for graduate employability - Ismail, Shaira; Abd Rahman, Nurul Hayani; Rezo, Khairul Hidayat; Ishak, Aniza @ Marzita; Shafie, Nani Ilyana (Universiti Teknologi MARA, Kedah, 2024)
This research project seeks to develop a job-based curriculum framework that aligns graduates' Skills, Knowledge, Abilities, and other Attributes (SKAOs) with labor market requirements to enhance employability and increase their marketability. By examining job specifications (JS) and job descriptions (JD) from 3,000 job advertisements across platforms such as MyFutureJobs and JobStreet Malaysia, the study aims to identify the essential SKAOs required by industries. Higher Education Institutions (HEIs) are encouraged to adapt their curricula to reflect the demands of the workforce, ensuring that the education provided is dependable, reliable, and up-to-date. Data gathered from job advertisements will be corroborated through interviews with selected employers and Ministry of Human Resources (MOHR) personnel. This framework specifically targets jobless alumni and final-semester students from Northern Region public universities, offering training and development programs managed by UiTM Pulau Pinang Branch in collaboration with MOHR. By addressing gaps in SKAOs, this initiative aims to ensure graduates are well-prepared for the workforce, possessing the competencies needed to meet industry demands and securing immediate employment upon graduation.